Psychological Review of the Ideal Age for Marriage: A Literature Review - Abdul Kholik; Encup Supriatna (GoAcademica Research & Publishing, 2023)
There is a change in the age limit for marriage in Law Number 1 of 1974 concerning Marriage, which was originally 16 years for women and 18 years for men, replaced with 18 years for Men and Women in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage raises the question of whether the age of 18 is ideal for marriage? Moreover, there is a science that focuses on recognizing a person's soul, namely psychology, so if you look at it from a sociological perspective, the ideal age for marriage is 18 years old. From the results of the discussion, it was found that the ideal age for marriage for men and women is 17 years and above because the teenage phase has been passed so that the age of 18 years in the Law is considered ideal for marriage.